Numerical solutions of Fisher's equation with collocation method - Gulbahar, Sema; Yokus, Asif; Kaya, Dogan (Amer Inst Physics, 2015)
In this paper, the collocation method using radial basis functions is presented for a numerical solution of Fisher's equation. In the solution process, we use linearization techniques for non-linear term existing in the equation. Furthermore, the methods which are analyzed by the error norms L-2 and L-infinity and by matrix stability analysis are tested for numerical examples and results obtained by four radial basis functions from computer runs are compared.
International Conference on Advancements in Mathematical Sciences (AMS) -- NOV 05-07, 2015 -- Antalya, TURKEY
Keywords: Collocation methods; Finite difference method; Matrix stability analysis